Clinical trial to compare safety and tolerability between intravenous infusion and bolus intravenous injection of ApTOLL in healthy volunteers - Hernández-Jiménez, Macarena; Martín-Vílchez, Samuel; Mejía-Abril, Gina; Roman, Manuel; Luquero-Bueno, Sergio; Piñeiro, David; Ribó, Marc; Abad-Santos, Francisco; Ochoa, Dolores (Molecular therapy. Nucleic acids, 2025)
ApTOLL, a new modulator of Toll-like receptor 4, has demonstrated safety and efficacy in healthy subjects and in stroke patients; however, the route of administration used so far (30 min infusion) can potentially be an issue in the acute stroke units where “time is brain.” To safely reduce the time of administration in future clinical trials, a dose-ascending, open-label, phase I clinical trial was conducted in healthy subjects. The objective was to assess the safety and pharmacokinetics of ApTOLL when comparing intravenous infusion (30 min) vs. bolus intravenous injection (1–3 min). The study was divided into three periods: (1) volunteers received 0.1 mg/kg of ApTOLL as a slow intravenous infusion, (2) 0.1 mg/kg of ApTOLL was administered as a single bolus, and (3) subjects received 0.2 mg/kg as a single bolus injection. No adverse events related to ApTOLL administration at any dosing pattern were reported. Maximum concentration was detected at the end of the infusion/injection, and mean half-life was 9.5 h for both routes of administration. These results show that safety and pharmacokinetic profiles were comparable between intravenous infusion and bolus injection of ApTOLL, supporting a change of the route of administration for future clinical practice (ClinicalTrials.gov: NCT05569720). [Display omitted] ApTOLL aims to reduce brain damage after stroke, but its current way of infusion (30 min) could be an issue in stroke units. To reduce the time of administration, the APTABOLUS trial was conducted, showing that the safety and pharmacokinetics of 30 min infusion and 1–3 min bolus injection were comparable.